Heavy Oil Seapage Characteristic in Cipari Area, Banyumas Central Java - Jonathan Setyoko Hadimuljono; Desi Yensusnimar (Testing Center for Oil and Gas LEMIGAS, 2021)
Oil seepage in Cipari, Banyumas, Central Java, has long been known. Although, Its occurrence had been reported in several publications, it's properties and characteristic, have not been explained in detail. Therefore, through field geology observation and laboratory analysis, this paper attempts to describe the oil seep characteristic, possible source rock origin, and its relationship with geological features in the surrounding area. Picnometer analysis resulted that this oil seep can be classified as heavy oil with 12n API Gravity. Gas Chromatography (GC) & Gas Chromatography Mass Spectometry (GCMS) analysis revealed that Cipari oil seep is heavily biodegraded. Possible source rock of the oil seep was interpreted based on bicadinane and oleanane biomarkers, which indicated that source was deposited in fluvio-deltaic/transitional environment. Based on regional geology reference of Banyumas sub-Basin, it is inferred that the source rocks possibly shale or claystone of Paleogene sediment which was thermally mature, and deposited in transition to marine environment. Deep seated fault that extent from Majenang to Karangbolong areas is probably the main migration pathway of the oil seepage from the kitchen or deep reservoir to the surface. The Cipari anticline outcrop, which associated with faults and fractures, become the place where the oil seep occurs in the surface. Heavy biodegradation of the oil seep may possibly be accelerated by hydrothermal system during migration from the reservoir/kitchen area to the surface.